Predicting Intervention Effectiveness From Reading Accuracy and Rate Measures Through the Instructional Hierarchy: Evidence for a Skill-by-Treatment Interaction. Issue 2 (1st June 2017) - Szadokierski, Isadora; Burns, Matthew K.; McComas, Jennifer J.
Abstract: The current study used the learning hierarchy/instructional hierarchy phases of acquisition and fluency to predict intervention effectiveness based on preintervention reading skills. Preintervention reading accuracy (percentage of words read correctly) and rate (number of words read correctly per minute) were assessed for 49 second- and third-grade students who then participated in a brief experimental analysis to determine whether they responded best to an acquisition (modeling) or a fluency (repeated reading) intervention package. Analyses indicated significant preintervention differences between students who responded to each intervention package. Preintervention accuracy and rate predicted the intervention to which students would better respond. Finally, a potential criterion (i.e., reading 85% of the words correctly with 32 words read correctly per minute) differentiated whether the students would benefit more from an acquisition or a proficiency intervention, supporting a skill-by-treatment interaction framework for reading.